2021
DOI: 10.3390/rs13234952
|View full text |Cite
|
Sign up to set email alerts
|

Driving Forces of the Changes in Vegetation Phenology in the Qinghai–Tibet Plateau

Abstract: Phenological change is an emerging hot topic in ecology and climate change research. Existing phenological studies in the Qinghai–Tibet Plateau (QTP) have focused on overall changes, while ignoring the different characteristics of changes in different regions. Here, we use the Global Inventory Modeling and Mapping Studies (GIMMS3g) normalized difference vegetation index (NDVI) dataset as a basis to discuss the temporal and spatial changes in vegetation phenology in the Qinghai–Tibet Plateau from 1982 to 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 64 publications
6
27
0
1
Order By: Relevance
“…Meanwhile, other studies have found a different conclusion in eastern China and Nanjing due to the complexity of the influencing factors [4,12,13]. Methods such as statistical analysis, correlation, and random forests were used to explore the temporal variation characteristics of phenology and response mechanisms [11,[14][15][16][17][18]. In terms of space, the study concluded that spring and autumn phenology in different regions are different with spatial heterogeneity [11,12,14,19].…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Meanwhile, other studies have found a different conclusion in eastern China and Nanjing due to the complexity of the influencing factors [4,12,13]. Methods such as statistical analysis, correlation, and random forests were used to explore the temporal variation characteristics of phenology and response mechanisms [11,[14][15][16][17][18]. In terms of space, the study concluded that spring and autumn phenology in different regions are different with spatial heterogeneity [11,12,14,19].…”
Section: Introductionmentioning
confidence: 98%
“…Many scholars have analyzed the spatiotemporal characteristics of regional phenology and concluded that spring phenology is advanced and that autumn phenology is delayed [4,9,11]. Meanwhile, other studies have found a different conclusion in eastern China and Nanjing due to the complexity of the influencing factors [4,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations